The relationship between sleep quality and physical activity among patients with heart failure: a cross-sectional study - Fatemeh Esnaasharieh; Mahlagha Dehghan; Parvin Mangolian Shahrbabaki (BMC, 2022)
Abstract Background Sleep disorders are one of the most common and annoying problems among patients with heart failure, which decrease their quality of life. Participation in physical activity is one of the most effective methods to reduce sleep disorders; however, few patients participate. This study was conducted to examine the relationship between physical activities and sleep quality among heart failure patients. Methods A convenience sample of 100 patients with heart failure referred to rehabilitation centers in southeastern Iran was used in this descriptive cross-sectional study. The Pittsburgh Sleep Quality Index and the Rapid Assessment of Physical Activity (RAPA) were used to collect data. The Spearman correlation coefficient and regression were used to analyze the data. The significance level was < 0.05. Results The results revealed that the mean score of sleep quality was 8.74 ± 2.83, with the majority of them (84.47%) having poor sleep quality. The mean score of physical activity was 2.59 ± 1.33, and the majority of them (95.15%) had sub-optimal physical activity. There was a significant and inverse relationship between the total scores of sleep quality and physical activity, and patients' sleep quality improved while physical activity increased. Physical activity, sex, history of heart surgery, and the stage of illness were found to account for 31% of the variances in patients' sleep quality. Conclusion The results of this study showed better sleep quality among patients who were more physically active. Given that the majority of patients with heart failure suffer from sleep disorders, patients' knowledge of physical activity should be increased to improve their quality of sleep and quality of life.